The Phenomenological Study of Online Marketing Adoption Among Farmers in Malang City - Azwar Saihani; Dea Edna Adinda (CV Projurnal Mitra Publikasi, 2025)
The digital transformation of agriculture in Indonesia faces a significant hurdle, marked by the low adoption rate of online marketing among farmers despite its potential to shorten supply chains and increase profitability. This study explores the lived experiences of farmers in Malang City, Indonesia, regarding the adoption of online marketing. Utilizing a qualitative phenomenological approach, in-depth interviews, observations, and documentation were conducted with six farmers purposively selected to represent diverse backgrounds, from conventional to millennial urban farmers. The analysis revealed six core themes: motivation driven by crisis and opportunity; a learning process heavily reliant on intergenerational assistance; a spectrum of marketing strategies from pure transaction to personal branding; positive economic impacts including margin increases of 40-50% and market diversification; persistent operational challenges such as logistics and digital reputation; and a fundamental identity transformation from traditional farmer to digital agripreneur. The findings highlight a digital divide not only in access and skills but also in the capacity to generate value from technology. This research enriches the Technology Acceptance Model by incorporating socio-cultural and intergenerational dimensions, introducing the concept of “facilitated adoption.” It concludes that online marketing adoption is a complex negotiation between tradition and modernity, producing heterogeneous farmer typologies. The study offers practical recommendations for local governments to create mentorship programs and for platforms to develop features responsive to diverse farmer needs, emphasizing that sustainable digital agriculture requires both technological infrastructure and social engineering.